An analysis of Ge’ez language heritage potential: traditional church schools and the practices of Ethiopian Orthodox Tewahido Churches. - Ertiban Demewoz Molla (Pharos Journal of Theology, 2018)
Traditional church schools and churches hold an irreplaceable share in the development of Ge’ez language heritage. The objective of the research was to analyze the potential and challenges of Ge’ez language heritage for the development of tourism in the traditional church schools, and the Ethiopian Orthodox Tewahido Churches of South Gondar Administrative Zone. To achieve this objective, the mixed research design was chosen. The respondents of the Questionnaire were 292. These were traditional church school students, calligraphers, and church servants. For the qualitative part, twenty persons (traditional church school teachers, faithful, and church and government bodies) were interviewed. Furthermore, documents were analyzed. Based on the result of the research, 86.55% of the respondents have confirmed that traditional church schools have high quality in human and physical resources and thus good Ge’ez language heritage potential. Moreover, 89.6% of the respondents have ascertained that some practices (mahlet service, the mass ceremony, prayers, preaching services) have very important potential as well. The respondents also confirmed that traditional church schools (relying on number and ability of students, books and basic need problem, modern education and globalization etc…) face very high challenges. Respondents have also witnessed that aspects including the number of church servants, and books that are read in other languages rather than Ge’ez are a challenge.Consequently, the study recommends that all the challenges should be met, and solutions promoted and managed with the cooperation of all the stakeholders for the development of Ge’ez language heritage.